Reduced expressions of apoptosis-related proteins TRAIL, Bcl-2, and TNFR1 in NK cells of juvenile-onset systemic lupus erythematosus patients: relations with disease activity, nephritis, and neuropsychiatric involvement - Liphaus, Bernadete L.; Silva, Simone C.; Palmeira, Patrícia; Silva, Clovis A.; Goldenstein-Schainberg, Claudia; Carneiro-Sampaio, Magda (Frontiers in Immunology, 2024)
Background Lupus pathogenesis is mainly ascribed to increased production and/or impaired clearance of dead cell debris. Although self-reactive T and B lymphocytes are critically linked to lupus development, neutrophils, monocytes, and natural killer (NK) cells have also been implicated. This study assessed apoptosis-related protein expressions in NK cells of patients with juvenile-onset systemic lupus erythematosus (jSLE) and relations to disease activity parameters, nephritis, and neuropsychiatric involvement. Methods Thirty-six patients with jSLE, 13 juvenile dermatomyositis (JDM) inflammatory controls, and nine healthy controls had Fas, FasL, TRAIL, TNFR1, Bcl-2, Bax, Bim, and caspase-3 expressions in NK cells (CD3−CD16+CD56+) simultaneously determined by flow cytometry. Disease activity parameters included Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) score, erythrocyte sedimentation rate, C-reactive protein level, anti-double strain DNA antibody level, complement fractions C3 and C4 levels. Results Patients with jSLE had a profile of significantly reduced expression of TRAIL, Bcl-2, and TNFR1 proteins in NK cells when compared to healthy controls. Similar profile was observed in patients with jSLE with active disease, positive anti-dsDNA, nephritis, and without neuropsychiatric involvement. Patients with jSLE with positive anti-dsDNA also had reduced expression of Bax in NK cells when compared healthy controls and to those with negative anti-dsDNA. Yet, patients with jSLE with negative anti-dsDNA had reduced mean fluorescence intensity (MFI) of Bim in NK cells compared to healthy controls. Patients with jSLE with nephritis also had reduced MFI of Fas in NK cells when compared to those without nephritis. In addition, in patients with jSLE, the proportion of FasL-expressing NK cells directly correlated with the SLEDAI-2K score (rs = 0.6, p = 0.002) and inversely correlated with the C3 levels (rs = −0.5, p = 0.007). Moreover, patients with jSLE had increased NK cell percentage and caspase-3 protein expression in NK cells when compared to JDM controls. Conclusion This study extends to NK cells an altered profile of TRAIL, Bcl-2, TNFR1, Fas, FasL, Bax, Bim, and caspase-3 proteins in patients with jSLE, particularly in those with active disease, positive anti-dsDNA, nephritis, and without neuropsychiatric involvement. This change in apoptosis-related protein expressions may contribute to the defective functions of NK cells and, consequently, to lupus development. The full clarification of the role of NK cells in jSLE pathogenesis may pave the way for new therapies like those of NK cell–based.